2008
DOI: 10.29140/jaltcall.v4n3.68
|View full text |Cite
|
Sign up to set email alerts
|

Using DynEd and ALC with low-level university freshmen

Abstract: In this paper we share our experience implementing a CALL project with first year, lower level, non-English major, university students, using two CALL packages popular in Japan: DynEd and ALC. In addition to comparing the pros and cons of both, we will also discuss how the project was launched and how it evolved over time. Implementing commercial CALL software in a classroom setting involved a number of challenges, both technical and pedagogical, necessitating a variety of adaptations to suit the needs of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…This theme is consistent with literature concerning common treatment of CALL systems (Bax, 2003, 2011; Brown et al, 2008; Bush, 2008). Instructors may be assuming that if RPG Sims are relegated to a supplementary or extracurricular role, they themselves would have very little direct interaction with such systems in practice.…”
Section: Results and Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…This theme is consistent with literature concerning common treatment of CALL systems (Bax, 2003, 2011; Brown et al, 2008; Bush, 2008). Instructors may be assuming that if RPG Sims are relegated to a supplementary or extracurricular role, they themselves would have very little direct interaction with such systems in practice.…”
Section: Results and Analysissupporting
confidence: 91%
“…Accordingly, Kim (2008) found that preservice EFL/ESL instructors tended to favor a teacher-centered classroom approach and marginalize CALL as supplementary material. The prevalence of this perception in Japan is indicated in the consignment of computer-supported learning systems to language labs as self-study material (Brown, Campbell, & Weatherford, 2008). At the same time, a CALL research community does exist in the form of academic societies such as the Japan Association of Language Teachers and CALL (JALTCALL), and the Japanese Association of Language Education and Technology (LET).…”
Section: Review Of Literaturementioning
confidence: 99%
“…When the findings related to the third research question of the study were analyzed, it was observed that, in terms of the placement test, the students achieved an average of 22 points (level of 0.05) on the test www.turkishstudies.net/education taken previously, 30 points (level of 0.10) on the test taken subsequent to the study. This result is supported by the results obtained from the literature (Bahri, 2016;Bingham & Larson, 2006;Brown et al, 2008;Huang & Wu, 2013;Inal & Korkmaz, 2019;Kagaoan et al, 2012;Kim et al, 2014;Tresnawati, 2011;Uras, 2018). On the other hand, even though the students were more successful after the blended teaching, it was seen that this achievement difference according to the DynEd guide was not at a significant level.…”
Section: Resultssupporting
confidence: 79%